(untitled) (Proceedings of the International Conference on Social Sciences, 2024)
Globally, deaths caused by road traffic injuries show an estimated a million deaths each year (WHO, 2018). Appallingly, road traffic injury is identified as the number one cause of death for children and young adults. Children are more vulnerable due to their physical fragility. Road safety education (RSE) is one of the integrative approaches that is chosen to intervene with the issue. RSE is any program or measure that focuses on promoting the knowledge of traffic rules and situations and the improvement of skills through training and experience. Malaysia implemented RSE at schools with the same aim. The present study aims to empirically analyse the association between the level of usage of the RSE module and the knowledge gained on road safety on the self-reported behaviour of students after a newly revamped RSE module was introduced in 2019. The students were selected by choosing sample schools from districts with the highest number of deaths among children aged seven to nine years old. It is hypothesised that the level of usage and the level of knowledge of these children is associated with their positive self-reported road safety behaviours. A multi-linear regression analysis showed that the model failed to predict self-reported behaviour as the model only explained 3.6% of the variance. Nevertheless, it was found that the usage level of RSE module significantly predicted the level of self-reported behaviour (B=0.191, p=0.000) but the level of knowledge failed to predict the self-reported behaviour (B=0.115, p=0.228). The results showed that the level of knowledge did not translate into behaviour. Continuous empirical study is essential to be conducted to ensure the program is guided by science to ensure the most effective implementation.